The Influence of Work-Life Balance and Work Discipline on Employee Engagement Mediated by Employee Job Satisfaction at the BMKG Manado Geophysics and Climatology Station - Moh Dewa Sataruno; Irvan Trang; Jane Grace Poluan (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to determine the influence of Work-Life Balance and Work Discipline on Employee Engagement which is mediated by Employee Job Satisfaction at the BMKG Manado Geophysics and Climatology Station. Using quantitative methods, the sampling technique is non-probability sampling and the technique is saturated (quantity) sampling. The results of this research found that Work Life-Balance was proven to have a significant influence on Employee Engagement at the BMKG Manado Geophysics and Climatology Station, Work Life-Balance was proven to have a positive influence on Employee Job Satisfaction at the BMKG Manado Geophysics and Climatology Station, Work Discipline with Employee Engagement can mediated by Employee Job Satisfaction at BMKG Manado Geophysics and Climatology Station, Work Discipline is proven to have a positive influence on Employee Engagement at BMKG Manado Geophysics and Climatology Station, Work Discipline is proven to have a positive influence on Job Satisfaction of BMKG Manado Geophysics and Climatology Station employees, Job Satisfaction is proven has a positive influence on Employee Engagement of the BMKG Manado Geophysics and Climatology Station.